2003
DOI: 10.1080/1042819031000079140
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure Secondary to Imatinib Mesylate Treatment in Chronic Myeloid Leukemia

Abstract: A 58-year-old woman with chronic myeloid leukemia (CML), and previous intolerance to interferon was treated with the BCR-ABL tyrosine kinase protein inhibitor imatinib mesylate. Coincidentally, with the start of treatment, the patient developed acute renal failure, with acute tubular necrosis being observed on histopathology. Imatinib was stopped and three hemodialysis sessions were performed, which was followed by a progressive improvement of the renal function and normalization of the urine output. One year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 7 publications
1
41
1
Order By: Relevance
“…20) The first one could occur when imatinib is used for patients with chronic myeloid leukemia, and was unlikely in our patients. Therefore, renal dysfunction observed in this study was most likely attributable to tubular damage, reported as acute tubular necrosis, 21) tubular vacuolization, 22) and partial Fanconi syndrome. 23) Renal dysfunction induced by imatinib sometimes becomes severe enough so as to require hemodialysis or irreversible even after discontinuation.…”
Section: Discussionmentioning
confidence: 96%
“…20) The first one could occur when imatinib is used for patients with chronic myeloid leukemia, and was unlikely in our patients. Therefore, renal dysfunction observed in this study was most likely attributable to tubular damage, reported as acute tubular necrosis, 21) tubular vacuolization, 22) and partial Fanconi syndrome. 23) Renal dysfunction induced by imatinib sometimes becomes severe enough so as to require hemodialysis or irreversible even after discontinuation.…”
Section: Discussionmentioning
confidence: 96%
“…Electronic microscopy showed vacuoles in some tubular cells, suggesting proximal tubular injury. Imatinib induced tubular necrosis has also been reported by Foringer and Pou [70], necessitating hemodialysis. In addition, one case of thrombotic microangiopathy (TMA) with renal and extra-renal expression has been reported, requiring definitive hemodyalisis [71].…”
Section: Other Targeted Therapies and Renal Toxicitymentioning
confidence: 86%
“…In three biopsy-proven cases, there was evidence of tubular damage in the form of acute tubular necrosis (ATN) [51], tubular vacuolization [52], and partial Fanconi syndrome with apical vacuoles in some tubular cells under electron microscopy examination [53]. Imatinib can inhibit PDGF-dependent renal mesangial cell proliferation by inhibitory effects on the PDGF receptor.…”
Section: Acute Kidney Injurymentioning
confidence: 97%